«Dignitatis humanae personae magis in dies conscii»: La dignità della persona nell’insegnamento e nella tradizione giuridica della Chiesa cattolica - Ruscazio, Maria Chiara (Dignità umana, 2024)
The paper retraces the main steps in the progressive recognition of the concept of human dignity in the teaching of the Catholich Church; then it examines the content of the principle from the catholic point of view and gives some examples of its implementation in canon law. Finally, it offers some food for thought regarding the possibility of a dialogue between catholic and secular conceptions of human dignity.